Calculating osmotic pressure according to nonelectrolyte Wilson nonrandom factor model. (August 2014) - Li, Hui; Zhan, Tingting; Zhan, Xiancheng; Wang, Xiaolan; Tan, Xiaoying; Guo, Yiping; Li, Chengrong
Abstract The osmotic pressure of NaCl solutions was determined by the air humidity in equilibrium (AHE) method. The relationship between the osmotic pressure and the concentration was explored theoretically, and the osmotic pressure was calculated according to the nonelectrolyte Wilson nonrandom factor (N-Wilson-NRF) model from the concentration. The results indicate that the calculated osmotic pressure is comparable to the measured one.